2011
DOI: 10.1093/jxb/err346
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of serine residues in the N-terminus modulates the activity of ACA8, a plasma membrane Ca2+-ATPase of Arabidopsis thaliana

Abstract: ACA8 is a plasma membrane-localized isoform of calmodulin (CaM)-regulated Ca2+-ATPase of Arabidopsis thaliana. Several phosphopeptides corresponding to portions of the regulatory N-terminus of ACA8 have been identified in phospho-proteomic studies. To mimic phosphorylation of the ACA8 N-terminus, each of the serines found to be phosphorylated in those studies (Ser19, Ser22, Ser27, Ser29, Ser57, and Ser99) has been mutated to aspartate. Mutants have been expressed in Saccharomyces cerevisiae and characterized: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 41 publications
3
27
0
1
Order By: Relevance
“…ACA8 forms a protein complex with FLS2 and is involved in flg22‐inducible Ca 2+ signaling (Frei dit Frey et al ., ). flg22 treatment/perception induces phosphorylation at ACA8 S22, and this N‐terminal phosphorylation is important for the interaction of ACA8 with CALMODULIN (CaM), leading to ACA8 activation (Giacometti et al ., ). We found that RPS2 activation similarly induced S22 phosphorylation (Tables , S4), suggesting CaM‐mediated activation of ACA8 during both PTI and ETI.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…ACA8 forms a protein complex with FLS2 and is involved in flg22‐inducible Ca 2+ signaling (Frei dit Frey et al ., ). flg22 treatment/perception induces phosphorylation at ACA8 S22, and this N‐terminal phosphorylation is important for the interaction of ACA8 with CALMODULIN (CaM), leading to ACA8 activation (Giacometti et al ., ). We found that RPS2 activation similarly induced S22 phosphorylation (Tables , S4), suggesting CaM‐mediated activation of ACA8 during both PTI and ETI.…”
Section: Resultsmentioning
confidence: 97%
“…We found that RPS2 activation similarly induced S22 phosphorylation (Tables , S4), suggesting CaM‐mediated activation of ACA8 during both PTI and ETI. Interestingly, CPK16 can phosphorylate S22 of ACA8 in vitro (Giacometti et al ., ), suggesting a role of CPK16 in the PTI and ETI signaling pathways. CBL‐INTERACTING PROTEIN KINASE‐9 (CIPK9) in a complex with the plasma membrane Ca 2+ sensor CALCINEURIN B‐LIKE PROTEIN‐1 (CBL1) phosphorylates ACA8, thereby regulating its activity (Costa et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…(), [10] Giacometti et al . (), [11] Curran et al . (), [12] Bohmer & Romeis (), [13] Boudsocq et al .…”
Section: Structure and Regulation Of Cdpks/crksunclassified
“…Since both BRI1 and CLV1 are members of the large family of receptor-like kinases (RLK) (Gish and Clark 2011), the two pumps might be substrate of their kinase activity. In the case of ACA8 it is known that this pump is phosphorylated in vivo at several Ser residues in the regulatory N-terminus and that phosphorylation can affect both auto-inhibition and CaM-binding (Giacometti et al 2012 and references therein). Although most of these Ser residues are not conserved in ACA12, we cannot exclude that phospho- dephosphorylation might also impact ACA12 activity, and that the yeast expressed enzyme might have properties different from that expressed in planta.…”
Section: Discussionmentioning
confidence: 99%